Pembuatan Paving Block Dinding Beton Berbahan Baku Abu Boiler Limbah Sawit Sebagai Pengganti Parsial Pasir - Sri Wahyuni; Nina Veronika (Politeknik Kampar, 2021)
Indonesia as the largest palm oil producer in the world has problems with the amount of solid waste such as boiler ash that has not been utilized properly. This study aims to determine the effect of boiler ash on the resulting paving blocks and obtain the best paving block characteristics. Utilization of boiler ash from burning palm oil waste as a partial substitute for sand in the manufacture of concrete wall paving blocks is carried out in several stages of work, namely the stages of sifting samples, mixing, molding, drying and testing the resulting product. The making of concrete wall paving blocks is done by varying the boiler ash in the composition of the concrete mixture with the ratio of cement to boiler ash, namely 1:1, 1:2, 1:3, 1:4, and 1:5. Based on the results of characteristic testing that will be carried out on the concrete wall paving block products, which include compressive strength and absorption, the best results are obtained from the 1:1 treatment with the following characteristics: absorption capacity of 19.73% and compressive strength of 5.7 Mpa